CORRECTION OF ANTERIOR OPEN BITE BY MULTILOOP EDGEWISE ARCHWIRE (A CASE REPORT) - Eveline Hartanto; Erwin Siregar (Faculty of Dentistry, Universitas Indonesia, 2015)
This case report was a treatment of anterior open bite with multiloop edgewise archwire (MEAW). The patient was a class II skeletal pattern nineteen year old girl. The possible etiology of this case was sucking habit and skeletal dysplasia. In 14 months the ideal class I molar and canine relationship was achieved.